An Eco-Friendly, CMOS-Compatible Transfer Process for Large-Scale CVD-Graphene - Moon, Ji Yun; Kim, Seung Il; Son, Seok Kyun; Kang, Seog Gyun; Lim, Jae Young; Lee, Dong Kyu; Ahn, Byungmin; Whang, Dongmok; Yu, Hak Ki; Lee, Jae Hyun (Advanced Materials Interfaces, 2019)
Since the first realization of graphene synthesis through the chemical vapor deposition (CVD) method in 2009, CVD-graphene is regarded as a key material in the future electronics industry, and one that requires high standard characteristics. However, because graphene itself is not a semiconductor, therefore it does not have a bandgap, a promising application is considered to integrate its use with semiconductors, rather than completely replace Si or Ge. Although numerous methods for a clean and uniform graphene transfer process are developed, graphene growth and transfer methods that are applicable to current mainstream Si-based complementary metal-oxide-semiconductor (CMOS) manufacturing processes are not yet introduced. This study implements an eco-friendly and CMOS-compatible graphene transfer process through water-soluble inorganic MoO3 film as a supporting layer. Since the monolayer graphene is grown on hydrogen-terminated semiconductor Ge surface, the MoO3 thin film coated graphene is easily delaminated from the Ge substrate. The separated graphene could be transferred to arbitrary substrate without a chemical wet etching process, and the remaining Ge substrate could be employed for about 50 times multiple reuse for the growth of graphene, without degradation of the crystallinity of the graphene.
Keywords: Chemical vapor deposition methods; Chemical wet etching process; Complementary metal oxide semiconductors; Manufacturing process; MoO3; transfer; Transfer process; Watersoluble; chemical vapor deposition; graphene; MoO3; transfer; water soluble